Direct Strain and Stress Measurement for Prestressed Steel. - Isaak, Suhaila (2000)
Bridge assessment requires knowledge of the design prestress and of any losses that may occur since stressing. The knowledge on state of stress in prestressing wires of prestressed beams is a very important criteria when assessment is conducted on an existing prestressed concrete structures. The high initial stress could slowly decrease due to creep, shrinkage and relaxation, effects. The reduction in stress could also occur abruptly due to slippage and loss of concrete area. The development of electronic instruments that test, measure, and control industrial processes has gone through a rather impressive growth pattern in recent years. In most industrial applications, the requirement of effective measurement method is very essential. In general, the strain gauge only measures the change of strain and stress due to loading unless it has been fixed in the steel structure before the steel is stressed. Until now, there are no practical non-destructive methods for measuring residual stress. The hole drilling strain gauge method can be used but destructive in nature. To date, the non-destructive stress measurement of prestressed steel has not yet been established after the steel has been stressed. Therefore, the purpose of this project is to develop the non-destructive residual stress measurement technique for prestressed steel by using resistance measurement as a tool for determining the stress value. Experimental tests were carried out to find a relationship between stress and resistance for three types of steel such as prestressing steel wire, prestressing steel strand and high tensile steel plate. The stress and resistance relationships obtained from the experiment have been analyzed by using statistical analysis. It was found that resistance in the prestressed steel is proportional to the applied stress. Based on the stress and resistance relationships obtained from the three types of steel specimens, a software was develop by using Visual Basic to compute the stress value for the measured resistance in the prestressed steel. For the time being, the resistance value is keyed in but should later be able to be improved, so that it will read directly from the interfacing circuit.